2015
DOI: 10.1002/hyp.10641
|View full text |Cite
|
Sign up to set email alerts
|

Modelling temperature change downstream of forest harvest using Newton's law of cooling

Abstract: We adapted Newton's law of cooling to model downstream water temperature change in response to stream-adjacent forest harvest on small and medium streams (average 327 ha in size) throughout the Oregon Coast Range, USA. The model requires measured stream gradient, width, depth and upstream control reach temperatures as inputs and contains two free parameters, which were determined by fitting the model to measured stream temperature data. This model reproduces the measured downstream temperature responses to wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 30 publications
7
23
0
Order By: Relevance
“…Several studies have documented cooling gradients of warmed water flowing downstream from openings into reaches with closed forest canopies; however, the magnitude of cooling effects have been highly variable, ranging from 2.0 to 9.2 °C km −1 (Broadmeadow, Jones, Langford, Shaw, & Nisbet, ; Keith et al, ; Story et al, ). Davis et al () used Newton's law of cooling to develop an empirical model, which estimated that maximum stream temperature would decline ~50% at a distance ~300 m downstream from a harvest. They attributed the principal determinants of variability in the actual cooling gradient to the downstream width, depth, and channel gradient (Davis et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented cooling gradients of warmed water flowing downstream from openings into reaches with closed forest canopies; however, the magnitude of cooling effects have been highly variable, ranging from 2.0 to 9.2 °C km −1 (Broadmeadow, Jones, Langford, Shaw, & Nisbet, ; Keith et al, ; Story et al, ). Davis et al () used Newton's law of cooling to develop an empirical model, which estimated that maximum stream temperature would decline ~50% at a distance ~300 m downstream from a harvest. They attributed the principal determinants of variability in the actual cooling gradient to the downstream width, depth, and channel gradient (Davis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Oregon, California, British Columbia, and elsewhere have also demonstrated both natural stream cooling in a downstream direction (Fullerton et al, ; Madej, Currens, Ozaki, Yee, & Anderson, ) and cooling of warmed water flowing from a stream reach draining a clear‐cut back into a closed canopy (Keith, Bjornn, Meehan, Hetrick, & Brusven, ; McGurk, ; Story et al, ). Although there is growing recognition of the high degree of variability in longitudinal stream temperature dynamics (Davis, Reiter, & Groom, ; Ebersole, Liss, & Frissell, ; Fullerton et al, ), it is increasingly important to determine the magnitude, spatial extent, and drivers of the downstream transmission of warmer stream water following disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al . () developed a mechanistic model predicting changes in stream temperature downstream of harvest and predicted that 50% (range = 82% to < 1%) of the temperature increase would persist downstream after streams flowed through 300 m of unharvested riparian forest.…”
Section: Methodsmentioning
confidence: 99%
“…Post-harvest stream shade was an important variable for a statistical model of stream temperature increases; shade levels were positively related to the remaining riparian stand basal area and, more weakly, inversely related to tree height. Davis et al (2016) developed a mechanistic model predicting changes in stream temperature downstream of harvest and predicted that 50% (range = 82% to < 1%) of the temperature increase would persist downstream after streams flowed through 300 m of unharvested riparian forest.…”
Section: Study Sites and Background Informationmentioning
confidence: 99%
“…Stream temperature response to natural and anthropogenic disturbances can be complex and nonlinear (Davis, Reiter, & Groom, ; Groom, Dent, & Madsen, ; Groom, Dent, Madsen, & Fleuret, ; Steel, Beechie, Torgersen, & Fullerton, ). However, the complexity of thermal responses to disturbance can be oversimplified when responses are represented by a single metric, such as a daily, weekly, or monthly maximum or minimum temperatures.…”
Section: Introductionmentioning
confidence: 99%